History of Islamic Economic Law Development in Indonesia - Intan Muthoharoh; Mohammad Ghozali (Journal of Islamic Economics Lariba, 2019)
The development of economy in the world is increasingly developed and enlarged. If there are no things that limit the use or implementation of it, it will give rise to things outside the rules of human life. Then it takes the expected norms could be disallowed in order that human beings act reasonable and not excessive. Because if not, it will soon be a contradiction and each individual to competite and to earn a profit of-magnitude. Economic Law existing in Indonesia can be referred to the book of the law of civil law and several articles on positive law. However, as a man of religion Islam, one must refer to the main reference in the form of propositions as Syar'iyah, like in the Qur'an and Hadith. Finally, in addition to the more needs is fullfilled, Proved that the economic Laws of Islam are also increasingly needed. Then the Islamic economic laws appear in society. And on the discussion this time, author tries to explain and discuss the historical development of Law, about the Islamic Economy.